(3MRH CHj MeRI GdZRGdjs - (3CHh MeRI GdZRGdjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdQMef GdQMje eGdc jhe GdOjf EjGc fYHO hEjGc fSJYjfs
(3BNQgG (B:s
(3Ef QHj Ydi UQGW eSJbje hGddg ef hQGFge eMjW Hd gh bQBf eLjO aj dhM eMahX hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg JSdjeG cKjQG Edi jhe GdOjf hGdMeO ddg QH GdYGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs